University Academic Reputation as a Leadership Factor in the Global Educational Market - N. L. Antonova; A. D. Sushchenko (Высшее образование в России)
The article discusses the university academic reputation as an indicator of its leadership in the global education services market. In the international rating systems for assessing the universities, academic reputation is one of the main indicators of status and prestige. Most higher education experts who look at the state of modern universities recognize that this factor is a key to attract the attention of the world academic community, industrial stakeholders, investors, prospective students and their parents to the university. We analyze the factors that improve university academic reputation using sources of empirical data such as QS World University Rankings database for 2017–2019 (open data analysis method), as well as the sociological research results including the opinions of experts (n = 5) (semi-structured interviews were selected as an appropriate method of data collection). The study results showed that China’s universities occupy a leading position. The key conclusion of the study is that the high academic reputation is one of the basic indicators of a university’s position in the global educational services market, but for leading universities it is a stigma reducing the need for innovation and the educational process development. BRICS Universities that create or change strategic development programme should be oriented towards achieving the leadership positions by not only institutional rankings but also subject and broad subject area rankings. This is a good indicator of the academic reputation growth for university, and it can be considered as a qualitative result of its goals and efficiency achieving in general.